Competing for Consciousness: Prolonged Mask Exposure Reduces Object Substitution Masking - Goodhew, S.; Visser, T.; Lipp, Ottmar; Dux, P. (2011)
In object substitution masking (OSM) a sparse, temporally trailing 4-dot mask impairs target identification, even though it has different contours from, and does not spatially overlap with the target. Here, we demonstrate a previously unknown characteristic of OSM: Observers show reduced masking at prolonged (e.g., 640 ms) relative to intermediate mask durations (e.g., 240 ms). We propose that with prolonged exposure, the mask's visual representation is consolidated, which allows processing of the lingering target icon to be reinitiated, thereby improving performance. Our findings suggest that when the visual system is confronted with 2 temporally contiguous stimuli, although one may initially gain access to consciousness above the other, the "losing" stimulus is not irreversibly lost to awareness. © 2010 American Psychological Association.